KEPASTIAN HUKUM KEWENANGAN PERADILAN MILITER DALAM MENGADILI PERKARA KONEKSITAS TERHADAP PENYERANGAN POLSEK CIRACAS (PUTUSAN DILMIL II 08 JAKARTA No. 232-K/PM. II-08/AD/XII/2020 – Tanggal 29 April 2021) - M Rizky Aulia Hakim; R Rahaditya (Fakultas Hukum Universitas Tarumanagara, 2021)
Article 89 paragraph (1) of the Criminal Procedure Code (KUHAP), criminal acts committed jointly by those belonging to the General Courts and Military Courts. To find out the legal provisions, to find out the mechanism for implementing the application of Civil and Military Justice, and to find out what obstacles arise in the implementation of Legal Certainty on the Authority of the Military Courts in Triing Connectivity Cases Against the Ciracas Police Sector Attack. Method or methodology is defined as the logic of scientific research, study of procedures and techniques. Research is essentially a series of scientific activities and therefore uses scientific methods to explore and solve problems, or to find a truth from existing facts. Crime is an eternal problem in human life, because crime develops in line with the development of human civilization. This also means that crime is a human problem from time to time. Crime is a phenomenon and social reality that causes bad feelings for the life of every human being. Evil often comes we cannot avoid, so we must be able to face the evil (Like it or Not). The incidence of crime has disturbed the community. A lot of money and energy has been spent to tackle the problem of crime, but the results have not been satisfactory. In fact, there is a tendency for the numbers to increase in some areas, both in terms of quality and quantity.